2013
DOI: 10.1016/j.molcel.2013.01.024
|View full text |Cite
|
Sign up to set email alerts
|

ZKSCAN3 Is a Master Transcriptional Repressor of Autophagy

Abstract: Summary Autophagy constitutes a major cell protective mechanism eliminating damaged components and maintaining energy homoeostasis via recycling nutrients under normal/stressed conditions. Although the core components of autophagy have been well studied, regulation of autophagy at the transcriptional level is poorly understood. Herein, we establish ZKSCAN3, a zinc-finger family DNA-binding protein, as a transcriptional repressor of autophagy. Silencing of ZKSCAN3 induced autophagy and increased lysosome biogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
249
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(253 citation statements)
references
References 37 publications
3
249
0
1
Order By: Relevance
“…Several transcription factors and molecules have been reported to induce or regulate the transcription of autophagy genes in various steps of autophagy and lysosome biogenesis. [48][49][50] Our data provide evidence that PPARGC1A, induced by AICAR-induced AMPK activation, triggers antimicrobial activity, of which at least one mechanism is the CEBPB-mediated induction of autophagy genes to induce antibacterial autophagy. It has been shown that increased PPARGC1A expression is strictly dependent on the binding of CEBPB to the proximal PPARGC1A promoter in 3T3-L1 preadipocytes.…”
Section: Discussionmentioning
confidence: 65%
“…Several transcription factors and molecules have been reported to induce or regulate the transcription of autophagy genes in various steps of autophagy and lysosome biogenesis. [48][49][50] Our data provide evidence that PPARGC1A, induced by AICAR-induced AMPK activation, triggers antimicrobial activity, of which at least one mechanism is the CEBPB-mediated induction of autophagy genes to induce antibacterial autophagy. It has been shown that increased PPARGC1A expression is strictly dependent on the binding of CEBPB to the proximal PPARGC1A promoter in 3T3-L1 preadipocytes.…”
Section: Discussionmentioning
confidence: 65%
“…18 In higher eukaryotes the family of FOXO transcription factors, GATA1 as well as the master regulator TFEB, activate autophagy, [19][20][21] while ZKSCAN3 and GATA4 are involved in the repression of mammalian autophagy-related genes. [22][23] In yeast, recent studies characterized Ume6 and Pho23 as transcriptional repressors of ATG genes and negative regulators of autophagy. 24,17 Nevertheless, very few transcription factors involved in the regulation of the expression of ATG genes in either yeast or mammals are known.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it was recently shown that the transcription factor ZKSCAN3 inhibits lysosomal biogenesis in HeLa cells. 97 Whether a pathway counteracting TFEB also exists in osteoclasts is not known, but one can speculate that the tight control of the balance between this putative pathway and TFEB will be critical to bone mass maintenance.…”
Section: Transcriptional Control Of Lysosomal Biogenesis In Osteoclastmentioning
confidence: 99%